Revitalization of Public Spaces as a High Priority Strategy for European Cities - Kozlova, Lyudmila (project baikal, 2013)
Over the last few decades, public spaces have been suffering from a progressive dystrophy. Prevalence of private cars in the absence of a good alternative to public transport and fragmentation of the city in the absence of its proper complex organization do a lot of harm to the city’s image.Many foreign cities started to value urban public spaces and to revitalize them about forty years ago. Examples of successful cities and various inspiring decisions encourage us to create a city structure as a place where people meet. Each city has an individual approach, but common features of the cities are: aspiration to create a comfort environment for a human being, a strong leader who can realize this idea and sequential and decisive actions to create a humane city for people.
Keywords: public space; identity; urban environment; city development strategy; pedestrian streets